2021
DOI: 10.3390/su13116365
|View full text |Cite
|
Sign up to set email alerts
|

Relationships and the Determinants of Sustainable Land Management Technologies in North Gojjam Sub-Basin, Upper Blue Nile, Ethiopia

Abstract: Sustainable land management (SLM) is a leading policy issue in Ethiopia. However, the adoption and continuous use of SLM technologies remain low. This study investigates the interrelationship of adopted SLM technologies and key factors of farmers’ decisions to use SLM technologies in the North Gojjam sub-basin of the Upper Blue Nile. The study was based on the investigation of cross-sectional data obtained from 414 randomly selected rural household heads, focus group discussions, and key informant interviews. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 50 publications
11
20
1
Order By: Relevance
“…According to Asfaw and Neka (2017) and Nkonki-Mandleni et al (2022), households headed by women are less likely to invest in SWC structural maintenance due to a lack of labor, less access to information and the fact that they bear additional in-house responsibilities such as cooking and taking care of the family members. This result is consistent with previous research (Gedefaw et al, 2018;Limani, 2018;Ewunetu et al, 2021;Oduniyi, 2022), which found that male-headed households are more likely to use structural SWC practices but contradicts the findings of other studies (Atnafe et al, 2015;Belachew et al, 2020) that more female-headed households are probably continuing with technology use than males.…”
Section: Sexsupporting
confidence: 85%
See 3 more Smart Citations
“…According to Asfaw and Neka (2017) and Nkonki-Mandleni et al (2022), households headed by women are less likely to invest in SWC structural maintenance due to a lack of labor, less access to information and the fact that they bear additional in-house responsibilities such as cooking and taking care of the family members. This result is consistent with previous research (Gedefaw et al, 2018;Limani, 2018;Ewunetu et al, 2021;Oduniyi, 2022), which found that male-headed households are more likely to use structural SWC practices but contradicts the findings of other studies (Atnafe et al, 2015;Belachew et al, 2020) that more female-headed households are probably continuing with technology use than males.…”
Section: Sexsupporting
confidence: 85%
“…In other words, adoptions of technology are not mutually exclusive or independent of each other (Amare et al, 2014;Mengistu and Assefa, 2019). Second, there are complementarities among SWC measures as far as factors affecting adoption statuses are concerned (Sileshi et al, 2019;Ewunetu et al, 2021). The sections that follow present the results and discussions made based on cross-sectional household survey data.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…However, fertilizer was negatively correlated with manure use indicating that farmers, on average, use manure and fertilizer as substitutes rather than complements. Similar results were documented in studies on Ethiopian maize production [3,7,30,40].…”
Section: Descriptive Resultssupporting
confidence: 89%